"Pacing does help you get your life back": The acceptability of a newly developed activity pacing framework for chronic pain/fatigue. (6th May 2021) - Antcliff, Deborah; Keenan, Anne‐Maree; Keeley, Philip; Woby, Steve; McGowan, Linda
Abstract: Objectives: We have developed and feasibility tested an activity pacing framework for clinicians to standardise their recommendations of activity pacing to patients with chronic pain/fatigue. This study aimed to explore the acceptability and fidelity to this framework in preparation for a future trial of activity pacing. Design: Acceptability and fidelity were explored using semi‐structured interviews. Data were analysed using framework analysis. Participants: Patients who attended a rehabilitation programme for chronic pain/fatigue underpinned by the framework, and clinicians (physiotherapists and psychological wellbeing practitioners) who led the programmes. Results: Seventeen interviews were conducted, involving 12 patients with chronic pain/fatigue and five clinicians. The framework analysis revealed four deductive themes: (1) Acceptability of the activity pacing framework, (2) Acceptability of the feasibility study methods, (3) Processes of change and (4) Barriers and facilitators to activity pacing; and one inductive theme: (5) Perspectives of patients and clinicians. Conclusions: The activity pacing framework appeared acceptable to patients and clinicians, and adherence to the framework was demonstrated. Processes of behaviour change included patients' regulation of activities through activity pacing. Barriers to pacing included work/social commitments and facilitators included identifying the benefits of pacing on symptoms. Different perspectives emerged between clinicians and patients regarding interpretations of symptom‐contingent and quota‐contingent strategies. The framework recognises fluctuations in symptoms of chronic pain/fatigue and encourages a quota‐contingent approach with flexibility. Future work will develop a patient friendly guide ahead of a clinical trial to explore the effects of pacing.